ORGANIZATION AND TECHNOLOGICAL STUDIES ON BUILDING RECONSTRUCTION USING CONVENTIONAL AND MODERN METHODS (Academic journal Industrial Machine Building Civil Engineering, 2017)
This article represents a short organization and technological analysis of finalizing theconstruction, using both conventional work materials and modern lightweight structures of fastassembling. The studies are done on the basis of «L» teaching block, which is in PoltavaNational Technical Yuri Kondratyuk University. Results of the study showed that it needsreconstruction. All-inclusive organization and technological and economical comparison ofthese two variants of the buildup proved that it is more advanced to carry out building worksusing modern technologies, even though they need more manpower effort and are moreexpensive. Nowadays we can observe a tendency to widely use fast mounting structures and itwill only become more wide-spread in the future, which will inevitably result in bothtechnologies and engineer construction equipment cheapening.Keywords: reconstruction, erecting, conventional work materials, light gauge steelframing, thermal modernization.